RELEVANSI SISTEM PENDIDIKAN PESANTREN TRADISIONAL DALAM ERA MODERNISASI (Studi Kasus Ponpes Miftahul Ulum Bettet Pamekasan) - Sahibuddin, Sahibuddin (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2017)
The modernization era, the existence of traditional boarding school be questionable of many parties about the relevance to be retained. In exception of the advantages education systems of the traditional boarding school, make it is able to survive and remain necessary in the modernization era. However, there are a number of modernization challenges are faced by schools today, one of them is going to meet the demands of skilled personnel in modern life sectors. In connection with this, schools are expected to contribute the human resources needed in modern life. Therefore, schools need to make change, especially concerning the provision of education that can still survive in the future. Of course the change was to stick to the rules "al-muhâfazhatu 'ala al-Qadim al-Salihwa al-akhdzu bi al-Jadid al-ashlah" (maintaining the good things that have been there and develop new things are better). The boarding school‟s development in the future can be carried out by a traditional boarding school that are not absolute. Efforts are made by the way of advance boarding identify with both of its assets, and then develop a modern way without changing the original boarding school shape. It requires a very creative and full of wise efforts, in addition it should be began by raising awareness that the change is very decisive, useful, and important.